Fortis-lenis vs voiced-voiceless plosives in Welsh - Asmus, Sabine; Jaworski, Sylwester; Baran, Michał (LingBaW. Linguistics Beyond and Within, 2020)
This paper questions the voiceless-voiced distinction of Welsh consonants and claims that the fortis-lenis distinction is more appropriate for the description of the language. In light of research results of theoretical as well as experimental investigations into Welsh, e.g. the vowel-coda length dependence discovered by Asmus and Grawunder (2017), advocated further research into that matter, seeing also that the fortis-lenis distinction establishes a firm link to focal properties of Welsh, such as morpheme-initial consonant mutations (mICM). It was, therefore, decided to look at potential phonetic features that would contribute to the postulated distinction. These features are aspiration, voicing, hold phase duration and the centre of gravity (abbreviated to CoG) in the articulation of Welsh plosives. Preliminary results of the study discussed in this paper were summarised in “Fortis-lenis or Voiced-voiceless – features of Welsh consonants” (Asmus et al. 2019). However, expanding our research has yielded more comprehensive findings. As a result, it appears that the two series of plosives under review are different in terms of all features studied, but it is aspiration that is of major importance (thus confirming classifications of Welsh as an aspiration language).